Pengaruh Kampanye Public Relations #Scientistganteng Terhadap Brand Awareness (Survei pada Followers Twitter @Whitelab_Id) - Dhea Aqshalnawitri; Siska Yuningsih (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The #ScientistGanteng campaign is a public relations campaign created by the Whitelab brand which aims to introduce a new Brand Ambassador who is a Korean idol, model, and actor, Sehun EXO. In addition to introducing the Brand Ambassador, the campaign was also used as a means of launching a new product called A Dose+ Glowing Serum. The purpose of this study was to measure how much influence a public relations campaign has on Whitelab's local skincare brand awareness. The population in this study was conducted on Twitter followers @whitelab_id with a sample of 97 respondents. The theories used in this study are public relations campaign theory (cognitive, affective, and conative) and brand awareness theory (unaware of brand, brand recognitions, brand recall, and top of mind). This research uses a quantitative approach with a survey method. The result of this study is that there is a moderate influence between the #ScientistGanteng Campaign on Brand Awareness of Whitelab local skincare which has a value of 0.542 or 54.2%, which means that Brand Awareness is influenced by 54.2% of the Public Relations Campaign and the rest is influenced by other variables not included in the study.